A willing slave: reflections on e-books. Issue 4 (4th July 2017) - Czarniawska, Barbara
ABSTRACT: This text is a personal confession projected at the background and history of e-books. Like with any new technologies, their introduction evoked hopes and fears. As technical problems vanish, and new habits are forming, the readership of e-books grows.